Nursing of a pediatric patient with acute tonsillitis and sore throat treated by moving-cupping therapy in anterior cervical region (蜜芽罐咽部走罐治疗1例小儿急性扁桃体炎咽痛的护理体会) - WANG Cuiting (王翠婷); YIN Hailan (尹海兰) (中西医结合护理)
This paper summarized the nursing experience of a pediatric patient with acute tonsillitis and sore throat treated by Miya jar moving-cupping therapy in anterior cervical region. Key issues of nursing included nursing assessment, standard procedure of moving-cupping therapy in anterior cervical region and related health education. Under the guidance of the nursing by Traditional Chinese medicine syndrome differentiation, cupping therapy by moving Miya jar in anterior cervical region is effective to relieve the clinical symptom and improve the recovery of pediatric patients with acute tonsillitis and sore throat. (本文总结1例蜜芽罐咽部走罐治疗小儿急性扁桃体炎咽痛的护理经验, 包括护理评估方案、咽部走罐操作方法以及常规健康宣教等。基于中医辨证施护护理理论, 采取咽部走罐疗法, 能有效缓解小儿咽痛症状, 对促进患儿康复有积极作用。)